RpoS impacts global gene expression and carbon source utilization in Escherichia coli O104:H4 - Berger, Petya; Bosse-Plois, Karla; Pölking, Wolfgang; Loewe, David; Kouzel, Ian U.; Berger, Michael; Dobrindt, Ulrich; Mellmann, Alexander (Frontiers in Microbiology, 2026)
BackgroundEscherichia coli (E. coli) O104:H4 caused the 2011 enterohemorrhagic E. coli (EHEC) outbreak in Germany, which remains the outbreak with the highest incidence of hemolytic uremic syndrome worldwide. We recently identified an E. coli O104:H4 isolate carrying a single nucleotide polymorphism in the start codon (ATG > ATA) of rpoS, which encodes the alternative sigma factor RpoS, resulting in reduced RpoS levels and enhanced virulence gene expression.Methods and resultsGene set enrichment analysis further revealed that the rpoS ATG > ATA mutation was primarily associated with activation of numerous metabolic pathways and repression of carbon source utilization-related transporter and transcription factor genes. Consistently, BIOLOG phenotype microarrays showed that E. coli O104:H4 rpoS ATG > ATA assimilated amino acids and organic acids (TCA cycle substrates) more efficiently, whereas the wild type strain displayed stronger metabolic respiration with sugars and sugar derivatives, including constituents of the mucus. Deletion of rpoS (ΔrpoS) in E. coli O104:H4 Δstx2 resulted in a carbon source utilization profile similar to the one of rpoS ATG > ATA, as well as in enhanced growth in minimal medium supplemented with amino acids and reduced one with sugars. Moreover, co-culture experiments with E. coli O104:H4 Δstx2 and E. coli O104:H4 Δstx2 ΔrpoS revealed a strong competitive advantage of the ΔrpoS strain with the tested amino acids; however, no advantage of the rpoS-intact strain was observed with sugars.ConclusionOur findings elucidate the impact of RpoS on global gene expression and carbon source utilization in E. coli O104:H4, further underscoring its role as a central regulator in pathogenic bacteria.